0158 Work in heat: a challenge for the kidneys. (21st August 2017) - Jakobsson, Kristina; Lucas, Rebekah; Venugopal, Vidhya; Crowe, Jennifer; Dahlqvist, Camilla; Apelqvist, Jenny; Weiss, Ilana; Glaser, Jason
Abstract : An epidemic of chronic kidney disease of unknown aetiology (CKDu) has emerged during the last decades, first seen in agricultural and disadvantaged communities along the Central American Pacific coast but now also evident in other countries like Sri Lanka and east India. The aetiology is likely multicausal, but occupational and environmental factors are in focus - in Central America heat stress during strenuous physical work with repeated fluid losses, in Sri Lanka environmental contaminants and agrochemicals. CKDu is a silent disease until late stages. Thus, screening with blood and urine sampling is needed for early detection We now have good tools for CKDu research: Heat and humidity in the workplace can be monitored with affordable climatic loggers. Core body temperature can be exactly measured by swallowed sensors or estimated from heat strain models. Heart rate loggers and accelerometers enable estimations of workload. Exposure to toxins is assessed through environmental monitoring or by biomarkers of exposure. Standardised questionnaires for heat-related symptoms exist, and core protocols for assessment of renal function and kidney disease outcomes in epidemiological studies have been elaborated (the DEGREE initiative). Occupational epidemiologists have an important role in the battle against CKDu. Collaborative and comparable studies are needed, aligned with mechanistic understanding. Such studies range from population-based prevalence studies (including also migrant workforces) to studies of the effect of piecework in hot climates, and evaluations of interventions to prevent heat strain by access to water, shade and safe toiletry at the workplace.